Corporate governance, national governance and the performance of mergers and acquisitions - Andrade, Christian Mascarenhas (2025)
This thesis investigates how differences in corporate governance (CG) and national governance (NG), conceptualized as governance distance, relate to the outcomes of mergers and acquisitions (M&As), with particular emphasis on cross-border deals. Two competing perspectives are evaluated: Governance Alignment Theory, which predicts that similarity between governance systems fosters integration success, and Governance Transfer Theory, which posits that either superior acquirer governance can be imposed on weaker targets or that superior target governance can be imported by weaker acquirers to create value. Using a global dataset of 7,545 full mergers and acquisitions (20112020) across 67 acquirer and 126 target countries, post-merger performance is measured through adjusted EBITDA and return on assets (ROA) over three-year pre- and post-merger windows. Governance metrics are drawn from the LSEG G-Index (firm-level) and the World Banks Worldwide Governance Indicators (national-level). After data refinement, 664 complete observations were analyzed, including 184 cross-border transactions. The results support Governance Transfer Theory. Corporate governance distance emerges as a consistent and positive predictor of post-merger financial performance, mainly when acquirers with stronger governance impose or import higher standards on weaker targets. In most cases in the sample, the acquirer holds superior governance. Quadratic models provide weaker evidence of convexity: very large gaps may yield accelerating gains, as the scope for reform and value creation grows with disparity. National governance distance also relates to performance, but in a weaker and less consistent way, while interaction terms are generally not significant predictors. A follow-up event-study using a smaller sample comprising domestic and cross-border deals closed by U.S.-based acquirers yields less conclusive results. Inferences based on robust regressions that mitigate potential biases originating from atypical influential observations suggest that shareholders anticipate value-enhancing governance transfers, consistent with previous analyses. However, OLS regressions without accounting for potential outliers show no evidence, based on cumulative abnormal returns, that investors systematically price governance differences at the merger announcement, underscoring a possible disconnect between short-term market valuations and realized longer-term operational outcomes. The evidence suggests that governance similarity is less decisive than the ability of acquirers to either impose or import superior governance standards. Governance transfer, not alignment, is the mechanism that explains post-merger success, and its effects are possibly both asymmetric and nonlinear. These findings expand the theoretical understanding of governance in international M&A and highlight the importance of distinguishing between realized operational outcomes and market expectations.